The Problem of Poverty, Struggle Against it and Historical-Philosophical Aspects - Nizomiddinovich, Meliboev Azizjon (European Journal of Life Safety and Stability (2660-9630), 2023)
In the article, the problem of poverty, the fight against it, is the task of the peoples of the whole world reflected.